PENERAPAN MODEL DIRECT INSTRUCTION UNTUK MENINGKATKAN KINERJA GURU KELAS IX SMP NEGERI 25 PONTIANAK DALAM MENYUSUN RPP - Sari Putri , Devi Yanti (Yudha English Gallery, 2023)
Application of the Direct Instruction Learning Model to Improve the Performance of Class VIII and IX Teachers in Preparing RPPs at SMP Negeri 25 Pontianak. School Action Research. Pontianak: SMP Negeri 25 Pontianak, 2022. This research aims to improve the ability of class IX teachers in preparing lesson plans using the 2013 curriculum as many as 12 teachers at SMP Negeri 25 Pontianak using the Direct Instruction learning model. This school action research was carried out in two cycles. The steps of each cycle include planning, action, observation, and reflection. The participants are class IX teachers who teach using the 2013 curriculum at SMP Negeri 25 Pontianak for the 2023/2024 academic year and the principal of SMP Negeri 29 as collaborators. Data was obtained through observation, field notes and tests. The validity of the data was attempted by triangulation. Qualitative data is analyzed through data reduction, data presentation and verification, while quantitative data is analyzed descriptively by calculating the percentage of test results. The results of this research show that the use of the Direct Instruction learning model in preparing lesson plans shows increased results, which are indicated by increased self-confidence, a pleasant and relaxed learning atmosphere, learning motivation, and the teacher's ability to prepare lesson plans increases. In cycle II it increased again to 10 teachers (83.3%). Meanwhile, the average test score was 58.25 in the pre-cycle, increasing to 62.5 in cycle I and increasing even more in cycle II, amounting to 65.5. This is evidenced by the increasing ability of teachers in preparing lesson plans from 3 people (25%) who completed it in the precycle, increasing to 8 people (66.6%) in the first cycle.